Bilateral asymmetry and developmental plasticity of the humerus in modern humans. Issue 3 (18th January 2021) - Zelazny, Kaya G.; Sylvester, Adam D.; Ruff, Christopher B.
Abstract: Objective: This study investigates bilateral asymmetry in the humerus of modern human populations with differing activity patterns to assess the relative plasticity of different bone regions in response to environmental influences, particularly the biomechanical demands of handedness. Methods: External breadths, cross‐sectional properties, and centroid sizes were used to quantify directional and absolute asymmetry of humeral diaphyseal, distal periarticular, and articular regions in six populations with differing subsistence strategies (total n = 244). Geometric section properties were measured using computed tomography at six locations along the distal humerus, while centroid sizes of the distal articular and periarticular regions, as well as eight segments of the diaphysis, were extracted from external landmark data. Bilateral asymmetries were compared between populations and sexes. Each property was also tested for correlation with bilateral asymmetry at 40% of bone length, which has been shown to correlate with handedness. Results: Asymmetry is highest in the diaphysis, but significant through all distal bone regions. Asymmetry increases in the region of the deltoid tuberosity, and progressively declines distally through the shaft and distal periarticular region. Articular asymmetry is higher than periarticular asymmetry, approaching levels seen just proximal to the olecranon fossa, and is weakly but significantly correlated with diaphyseal asymmetry. Hunter‐gatherers from Indian Knoll have significantly higher levels of asymmetry than other groups and are more sexually dimorphic, particularly in cross‐sectional properties of the diaphysis. Conclusions: Humeral dimensions throughout the diaphysis, including regions currently used in taxonomic assignments of fossil hominins, likely respond to in vivo use, including population and sex‐specific behaviors. Abstract : External measurements, cross sections, and semilandmark subsets used to investigate asymmetries of the distal humeral diaphysis, metaphysis, an epiphysis in differing populations. Asymmetry progressively declines from the deltoid tuberosity through the distal periarticular region and then rises in the articular region.